‘World Will Never Be Same’: Phraseologisms during Coronavirus Pandemic - O. E. Chernova; A. A. Osipova; N. V. Pozdnyakova (Научный диалог)
Issues related to the semantics, structure and functions of new super-word linguistic units that have come into active use during the coronavirus pandemic are considered. Particular attention is paid to the statistics of searching the Internet for a certain phrase for a month and specific digital indicators of its existence as a stable one. The novelty of the research is seen in the fact that identifies phraseologisms of the late XX — early XXI centuries, which need a full-fledged phraseographic description (origin, semantics, examples of use). Phrasemes are combined by the authors into thematic groups: 1) remote work and study, 2) administrative measures to combat coronavirus, 3) features of a new disease and its treatment. It is shown that in the texts of mass communication Phrasemes perform nominative, communicative and pragmatic functions. Investigating stable turnovers, the authors dwell upon their structure, which is represented by three models. It is noted that the result of the work will be a dictionary of phraseological neologisms, which, along with others, will include units that appeared during the coronavirus pandemic.